Antidepressant Effects of South African Plants: An Appraisal of Ethnobotanical Surveys, Ethnopharmacological and Phytochemical Studies - Bonokwane, Melia Bokaeng; Lekhooa, Makhotso; Struwig, Madeleen; Aremu, Adeyemi Oladapo (Frontiers in Pharmacology, 2022)
Globally, the search for safe and potent natural-based treatment for depression is receiving renewed interest given the numerous side-effects associated with many existing drugs. In South Africa, the use of plants to manage depression and related symptoms is fairly documented among different ethnic groups. In the current study, we reviewed existing ethnobotanical, ethnopharmacological and phytochemical studies on South African medicinal plants used to manage depression. Electronic databases were accessed for scientific literature that meets the inclusion criteria. Plants with ethnobotanical evidence were subjected to a further pharmacological review to establish the extent (if any) of their effectiveness as antidepressants. Critical assessment resulted in 20 eligible ethnobotanical records, which generated an inventory of 186 plants from 63 plant families. Due to the cultural differences observed in the definition of depression, or lack of definition in some cultures, most plants are reported to treat a wide range of atypical symptoms related to depression. Boophone disticha, Leonotis leonurus and Mentha longifolia were identified as the three most popular plants, with over 8 mentions each from the ethnobotanical records. The dominant families were Asteraceae (24), Fabaceae (16), Amaryllidaceae (10), and Apocynaceae (10) which accounted for about 32% of the 186 plants. Only 27 (≈14.5%) of the plants have been screened for antidepressant activity using in vitro and in vivo models. Agapanthus campanulatus, Boophone disticha, Hypericum perforatum, Mondia whitei and Xysmalobium undulatum, represent the most studied plants. Phytochemical investigation on 9 out of the 27 plants revealed 24 compounds with antidepressant-like effects. Some of these included buphanidrine and buphanamine which were isolated from the leaves of Boophone disticha, Δ9- tetrahydrocannabinol, cannabidiol and cannabichromene obtained from the buds of Cannabis sativa and carnosic acid, rosmarinic acid and salvigenin from Rosmarinus officinalis, A significant portion (≈85%) of 186 plants with ethnobotanical records still require pharmacological studies to assess their potential antidepressant-like effects. This review remains a valuable reference material that may guide future ethnobotanical surveys to ensure their robustness and validity as well as database to identify promising plants to screen for pharmacology efficacy.